Two new species of Flavoperla (Plecoptera: Perlidae) from Shaanxi Province of China - Liu, Hao; Yan, Yanhua; Li, Weihai (Zootaxa, 2019)
Two new Perlidae stonefly species, Flavoperla furcomaculata sp. nov. and F. triangulata sp. nov. from the Qinling Mountains, Shaanxi Province, northwestern China are described. Their taxonomic relationships with other known similar Flavoperla species are discussed.